2011
DOI: 10.1007/s12603-011-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity exercise and protein supplement on muscle mass in ADL dependent older people with and without malnutrition—A randomized controlled trial

Abstract: A three month high-intensity functional exercise program did not increase the amount of muscle mass and an intake of a protein-enriched drink immediately after the exercise did not induce any additional effect on muscle mass. There were negative long-term effects on muscle mass and BW, indicating that it is probably necessary to compensate for an increased energy demand when offering a high-intensity exercise program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
118
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(118 citation statements)
references
References 33 publications
0
118
0
Order By: Relevance
“…Four studies were conducted in the USA [10, 11, 13, 18], two in Europe (Germany and Sweden) [12, 17] and the others in Japan [14-16]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies were conducted in the USA [10, 11, 13, 18], two in Europe (Germany and Sweden) [12, 17] and the others in Japan [14-16]. …”
Section: Resultsmentioning
confidence: 99%
“…The number of study subjects varied widely, from 57 [13] to 1,635 [10]. Five of the studies were conducted among subjects of both genders [10, 11, 14, 17, 18], while the remaining studies were conducted in females only. One study [13] described no information regarding the gender.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original article assessed the effect of high-intensity exercise and timed protein supplementation on the muscle mass and weight of very old aged people living in institutions (1). The trial failed to found any positive effects on muscle mass and body weight.…”
Section: Dear Editormentioning
confidence: 99%
“…Protein supplementation given to the intervention group contained only 14.8 g of protein and about 200 kcal of energy (1). This is far from a sufficient amount of energy and protein to build muscle or even to prevent muscle decline in older people, as Carlson et al has mentioned.…”
Section: Dear Editormentioning
confidence: 99%